If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -3y = 818 Solving -3x + -3y = 818 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. -3x + -3y + 3y = 818 + 3y Combine like terms: -3y + 3y = 0 -3x + 0 = 818 + 3y -3x = 818 + 3y Divide each side by '-3'. x = -272.6666667 + -1y Simplifying x = -272.6666667 + -1y
| (7n-6)+2=1 | | 375+12h=280+15h | | -10n+2(.9-9n)=5.8 | | 8x(x-5)=4x-10+3x-30 | | 12x+y=-60 | | -5(7-x+5x)= | | -5n+6=-35n-42-6n | | 16=[2w+w-1] | | 7y+27=6y-3 | | 3(60)-3x=99 | | 50+3x=14 | | 9a-9.4=8a+4.6 | | -6+x=19 | | -2-2x-5x=-37 | | 8(3-2)=104 | | (y^2-7y-5)-(-3y^2+3y-4)= | | 2(5r+45)=20(2r-24) | | 5n+7+n=3n-2+4n(2n+1) | | t=4+3x | | -10-(-5x)=5x | | 3x+11-x=8+4x-5 | | -4.4+6.2=5x-2.9-4x | | x=4+3t | | 2+0.5x=3-5x | | 7-3u^2=1 | | 50+3x=4 | | x+65+57=90 | | 7(9n-4)= | | 5=12(2cosx+sinx) | | 4x+9x-3x=37+3 | | Y=6x^2-13x-8 | | 2c+4d=4 |